2013
DOI: 10.1001/jamaneurol.2013.2110
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Mild Cognitive Impairment in Early Parkinson Disease

Abstract: Importance: Mild cognitive impairment (MCI) is common in Parkinson disease (PD), but the prognostic value of MCI in early PD is unknown. Objective: To examine the course of MCI and its progression to dementia in an incident PD cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
252
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(283 citation statements)
references
References 50 publications
(48 reference statements)
14
252
3
3
Order By: Relevance
“…24 A recent study of patients with early PD and shorter follow-up (3 years) found that 27% of patients with MCI developed dementia during this time period, with older age and both attention and verbal memory deficits predicting decline. 7 Although it has been hypothesized that some MCI subtypes presenting early in the disease course may be stable and not progress to dementia, 25 our findings suggest that if a patient with PD develops incident MCI, progression to dementia may be universal within 5 years. Progression to dementia may be particularly rapid in older patients (the mean age of our cohort at baseline was 69 years), although surprisingly age was not a significant predictor, perhaps due to the narrow age range of our cohort.…”
Section: Discussionmentioning
confidence: 64%
“…24 A recent study of patients with early PD and shorter follow-up (3 years) found that 27% of patients with MCI developed dementia during this time period, with older age and both attention and verbal memory deficits predicting decline. 7 Although it has been hypothesized that some MCI subtypes presenting early in the disease course may be stable and not progress to dementia, 25 our findings suggest that if a patient with PD develops incident MCI, progression to dementia may be universal within 5 years. Progression to dementia may be particularly rapid in older patients (the mean age of our cohort at baseline was 69 years), although surprisingly age was not a significant predictor, perhaps due to the narrow age range of our cohort.…”
Section: Discussionmentioning
confidence: 64%
“…Until recently, object recognition has not been well studied in PD. Studies using measures such as the Vision Object and Space Perception battery have shown inconsistent findings 36, 37. Recognition of embedded figures may be affected,13 and emotion recognition, a specialized form of object recognition, is impaired 14.…”
Section: Discussionmentioning
confidence: 99%
“…19 Three-year follow-up of 182 participants in the Norwegian ParkWest Study cohort showed that 10 of 37 subjects with PD-MCI at baseline had converted to PDD, compared to one of 145 with normal cognition, a relative risk of 39.2. 20 However, this study also found that 22% of PD-MCI subjects at baseline reverted to normal cognition, implying that PD-MCI can be reversible. The PD-MCI converters were significantly older and had significantly worse scores on tests of executive function at baseline compared to the PD-MCI reverters.…”
Section: Pd Mild Cognitive Impairmentmentioning
confidence: 56%
“…The PD-MCI converters were significantly older and had significantly worse scores on tests of executive function at baseline compared to the PD-MCI reverters. 20 More information is needed to understand the transition between normal cognition, PD-MCI and PDD. PD-MCI and PDD appear to share several risk factors such as level of education, 21 severity of motor deficit 22,23 and male gender.…”
Section: Pd Mild Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation